Technical violations and infractions are drivers of disengagement from methadone treatment among people with opioid use disorder discharged from Connecticut jails 2014-2018 - Phillip Marotta; Alissa Hass; Adam Viera; Molly Doernberg; Russell Barbour; Lauretta E. Grau; Robert Heimer (BMC, 2023)
Abstract Background We investigated the interaction between arrests for technical violations vs. receiving new charges with receiving community-based methadone treatment on time-to reincarceration (TTR) in a cohort of men with opioid use disorder (OUD) released from custody from two Connecticut jails from 2014 to 2018. Methods Hazard ratios (HR) were estimated for time to reincarceration for technical violations/infractions, misdemeanors only, felonies only, and both misdemeanors and felonies after adjusting for age, race/ethnicity, and receiving methadone treatment during incarceration or in the community following release. Moderation analyses tested the hypotheses that the benefits of receiving methadone in jail or the community on TTR were significantly different for people with only technical violations and infractions compared to misdemeanor and felony charges. Results In the sample of 788 men who were reincarcerated, 29.4% received technical violations with no new charges (n = 232) with the remainder of the sample receiving new charges consisting of 26.9% new misdemeanor charges, 6.5% felony charges, and 37.2% both felony and misdemeanor charges. Compared to men who received new misdemeanor charges, TTR was significantly shorter among those who received technical violations and infractions with no new charges amounting to a 50% increase in TTR (334.5 days, SD = 321.3 vs. 228.1 days, SD = 308.0, p < 0.001; aHR = 1.5, 95% CI = 1.3, 1.8, p < 0.001). TTR of men who resumed methadone and were charged with a new crime was 50% longer than those who resumed methadone and received technical violations/infractions with no new charges. (230.2 days, SD = 340.2 vs. 402.3 days, SD = 231.3; aHR = 1.5, 95%CI = 1.0, 2.2, p = 0.038). Conclusions Reducing technical violations may enhance the benefits of providing community-based methadone following release from incarceration on extending the time between incarcerations during the vulnerable time post-incarceration and reduce the burden on correctional systems.